Peran Brand Awareness dalam Meningkatkan Minat Beli Konsumen: Studi Pada Produk Air Minum Dalam Kemasan Merek UNESA - Hidayati, Rika Jannatul; Fahmi, Moh Farih (Universitas Serambi Mekkah, 2024)
In Indonesia, the demand for drinking water continues to increase. Packaged drinking water has become an alternative for people who have difficulty obtaining clean and safe water for consumption. During the last few years, various universities have begun to develop packaged water production as an effort to meet local demands and support environmental programs. One of them is the packaged drinking water product brand